EFEKTIVITAS E-MODUL AJAR TERDIFERENSIASI BERBASIS MODEL PEMBELAJARAN LDR (LEARN, DO, REFLECT) DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Khoerunnisa, Adinda; Dwi Puspita, Ryan; Dewi Nirmala, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school students’ mathematical problem-solving abilities play an important role in developing logical and creative thinking; however, these abilities are still not optimal due to limitations in learning models, teachers’ understanding of students’ needs, and the use of technology. Therefore, adaptive and contextual learning innovations are required, one of which is the development of a teaching e-module based on the LDR (Learn, Do, Reflect) model, designed to improve mathematical problem-solving abilities in an interactive and meaningful manner. This study aimed to examine the effectiveness and practicality of a differentiated teaching e-module based on the LDR (Learn, Do, Reflect) model in enhancing the mathematical problem-solving abilities of fifth-grade elementary school students. The study employed a research and development (R&D) approach using the ADDIE model and involved experts, teachers, and elementary school students. Effectiveness was tested through a quasi-experimental design, while practicality was evaluated using interviews, observations, student learning journals, and teacher questionnaires. The results indicated that the teaching e-module received highly positive responses and was effective in improving students’ mathematical problem-solving abilities, as evidenced by a significant difference between the experimental and control groups and a medium N-Gain value, indicating that the e-module is suitable for implementation in elementary school mathematics instruction.